Improving Motor Skills through Athletics: A Case Study of High School Students in Sumedang - Angga Nugraha; Subarna Subarna; Qays Banwan Shareef; Dilli Dwi Kuswoyo (Universitas Hamzanwadi, 2025)
The problem in this study is that the integration of athletics into the physical education curriculum in Indonesia, especially in areas such as Sumedang Regency, is often hampered by limited facilities and infrastructure. This has the potential to hinder the effective development of basic motor skills in high school students, which are the foundation for physical literacy and an active lifestyle. This study aims to evaluate the impact of a structured athletics training program on improving the motor skills of high school students in Sumedang Regency. The research method used a quasi-experimental design with a one-group pretest-posttest model. A total of 60 students (30 males, 30 females) aged 15-17 years from three high schools participated. Motor skills were assessed through a 30-meter sprint, standing long jump, and 2 kg medicine ball throw tests. Participants undergo an athletic training program for 6 weeks (3 sessions/week). The data were analyzed using a Paired Samples t-test. The results showed a very significant improvement (p < 0.001) in all three skill components. The average sprint time decreased from 5.87 to 5.41 seconds, the jump distance increased from 1.85 to 2.05 meters, and the throw distance increased from 4.12 to 4.56 meters. The effect size for all results was classified as large. The conclusion is that a structured athletic training program has been proven effective in improving the motor skills of high school students, even under limited facility conditions.